Induction Apoptosis of Erinacine A in Human Colorectal Cancer Cells Involving the Expression of TNFR, Fas, and Fas Ligand via the JNK/p300/p50 Signaling Pathway With Histone Acetylation - Lee, Ko-Chao; Lee, Kam-Fai; Tung, Shui-Yi; Huang, Wen-Shih; Lee, Li-Ya; Chen, Wan-Ping; Chen, Chin-Chu; Teng, Chih-Chuan; Shen, Chien-Heng; Hsieh, Meng-Chiao; Kuo, Hsing-Chun (Frontiers in Pharmacology, 2019)
Erinacine A, which is the major one of the bioactive diterpenoid compounds extracted from cultured mycelia of H. erinaceus, displays great anti-tumorigenic activity. However, the molecular mechanisms underlying erinacine A inducing cancer cell apoptosis in CRC remain unclear. This study shows that treatment with erinacine A not only triggers the activation of extrinsic apoptosis pathways (TNFR, Fas, Fas-L and caspases), but also suppresses the expression of anti-apoptotic molecules Bcl-2 and Bcl-XL via a time-dependent manner in DLD-1 cells. Furthermore, phosphorylation of Jun N-terminus kinase (JNK1/2), NFκB p50, p300 is involved in erinacine A-induced cancer cell apoptosis. Inhibition of these three signaling pathways by SP600125 (an inhibitor for JNK1/2), C646 (an inhibitor for p300), or PDTI (an inhibitor for NFκB) blocks erinacine A–induced transcriptional activation implicates histone H3K9K14ac (Acetyl Lys9/Lys14) of the TNFR, Fas, and Fas-L as promoters. Moreover, histochemical and immunohistochemical analyses revealed that erinacine A treatment significantly induced the TNFR, Fas, and Fas-L levels in the in vivo xenograft mouse model. Together, these results demonstrated an increase in the cellular transcriptional levels of TNFR, Fas, and Fas-L by erinacine A induction to cell apoptosis via the activation of the JNK, p300, and NFκB p50 signaling modules thereby providing a new mechanism for erinacine A treatment in vitro and in vivo.